En Bondes Längtan . A Farmer’s Desire - Rasmusson, Rebecka (Rasmusson, Rebecka, 2010)
Verzio9 FF Submission. Duration: 00:14:00 Knut is a farmer from southern Sweden who has lived all his life with the feeling that he was born in the wrong body. He didn't know what transsexualism was until after he turned fifty but now he wants to live fully as the woman he feels he is. The only thing he wants to keep is his name, because he grew fond of it, though the guy named Knut vanished over time. A warm humorous film about the search for gender identity and the courage to stand up for who you are.